The Formulation of Morality Crimes in Law No. 1 of 2023: A Criminal Law Study of the Risk of Overcriminalization and Legal Certainty - Natasa Belinda; Fero Sanjaya; Herlita Eryke (PALAR | PAKUAN LAW REVIEW, 2026)
Law No. 1 of 2023 on the Criminal Code brings fundamental reforms to Indonesia's criminal justice system, including the reclassification of moral crimes. The formulation of offenses such as adultery and cohabitation has sparked debate regarding the rational limits of criminalization in a state governed by the rule of law. This study aims to analyze the normative formulation of moral crimes in Law No. 1 of 2023, examine the potential for overcriminalization, and assess its implications for the principle of legal certainty. This study uses a qualitative descriptive method with a normative juridical approach through the analysis of legislation and a conceptual approach. The primary legal material is Law No. 1 of 2023, while the secondary legal material includes current literature and scientific articles. The results of the study show that the expansion of the scope of moral offenses has the potential to expand state intervention in the private sphere, even though it is formulated as a complaint offense. Several provisions still leave room for multiple interpretations that can affect the consistency of the application of the principles of legality and legal certainty. This study emphasizes the importance of limiting criminalization based on the principles of proportionality and ultimum remedy so that criminal law reform remains in line with the values of legal certainty and the protection of citizens' rights.   Keywords : Moral crimes, Overcriminalization, Legal certainty, Principle of legality, 2023 Criminal Code.